Common and country specific factors in the distribution of real wages - Eleni Chatzivgeri; Haroon Mumtazy; Daniela Tavasciz; Luigi Ventimigliax (Queen Mary University of London, School of Economics and Finance, 2018)
We use a dynamic factor model to consider if real wage growth in the US, UK and Germany at different percentiles of the distribution can be explained by factors that are common across countries or specific to each country. Our results suggest that common factors explain a large proportion of the movement in wages when considering the left tail of the distribution indicating that shocks that are common across countries are important for low wage households.
Keywords: C5; E1; E5; E6; 330; Household wages; dynamic factor model